(untitled) (Journal of Science and Technology Research, 2026)
Synthetic dyes conquered the natural colorants due to its outstanding properties of color matching, high clarities, better serviceability and ease of processing despite its adverse effect on environment. Jute fiber, the golden fiber of Bangladesh, is commercially dyed with hazardous synthetic dyes especially using basic dyes, which plays an adverse role on the environment. To overcome this issue, an attempt is made to apply an ecofriendly natural colorant extracted from green turmeric for the jute fabric to boost up the sustainable and cleaner wet processing of our golden fibre. In this study, the potentials of natural colorants extraction from green turmeric and consequent dyeing are evaluated. Natural colorants were extracted by facile boiling of green turmeric paste at 100℃ for 60 minutes in aqueous, acidic and alkaline media. The solid residues were then separated from the solution with the nylon strainer. Subsequently, scoured and bleached jute fabrics were dyed with the extracted colorants in exhaust dyeing method. To investigate the effects of different synthetic mordants, mordanting of jute fabric were done with potash-alum, tannic acid, ferrous-(II) sulfate heptahydrate, stannous-(II) chloride pentahydrate, potassium dichromate, and copper-(II) sulfate pentahydrate. The impacts of temperature, dyebath pH, mordants, and dyeing period were intensively observed to get optimum dyeing conditions. The impact of dyeing parameters was evaluated in terms of color strength (k/s value) and chromaticity of the dyed fabric. The results revealed that different mordants, temperature, pH and dyeing period showed significant effects on the color strength and chromaticity. Potash-alum, tannic acid, and copper-(II) sulfate pentahydrate mordanted jute fabrics exhibited good color fastness to wash with a grey scale ratting of 3-4 to 4, while other showed poor color fastness to wash. J. of Sci. and Tech. Res. 6(2): 55-64, 2025